2022
DOI: 10.2147/dddt.s325852
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives in the Treatment of Locally Advanced Basal Cell Carcinoma

Abstract: Basal cell carcinoma (BCC) is the most common cancer in Caucasians, and its incidence continues to rise. Generally, BCCs have good outcomes when diagnosed and treated early. However, 1–10% of patients will develop advanced disease due to either delays in accessing treatment or aggressive tumors that may be refractory to treatment. Locally advanced basal cell carcinomas (laBCCs) are large, aggressive, or recurrent tumors that have the potential to invade surrounding tissues including bone, cartilage, nerve, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…BCC metastases are rare, while cSCC can metastasize in 3-7% of cases [7]. Surgical excision is the primary treatment for both, though Mohs micrographic surgery and various destructive therapies like topical drugs, radiation therapy, and cryotherapy are also used based on tumor and patient factors [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BCC metastases are rare, while cSCC can metastasize in 3-7% of cases [7]. Surgical excision is the primary treatment for both, though Mohs micrographic surgery and various destructive therapies like topical drugs, radiation therapy, and cryotherapy are also used based on tumor and patient factors [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For BCC, understanding its pathogenesis, particularly the role of hedgehog (HH) signaling, led to hedgehog pathway inhibitors (HHIs) like sonidegib and vismodegib, which have shown effectiveness [7][8][9][10][11][12][13]. However, some patients do not respond well or tolerate HHIs, necessitating alternative treatments [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PD1i cemiplimab has been approved since 2021 for patients with aBCC intolerant to or progressive on treatment with HHIs. PD1i increase the T-cell-mediated immune response, thereby sustaining the endogenous antitumor activity [ 5 , 6 ]. It has been found that 31% of patients with laBCC and 24% with mBCC will respond to second-line treatment with cemiplimab after HHI.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that 31% of patients with laBCC and 24% with mBCC will respond to second-line treatment with cemiplimab after HHI. Even though PD1i pembrolizumab is at present not approved for treatment of aBCC, small studies and case series suggest a similar response rate in aBCC pretreated with HHI compared to cemiplimab [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%